Highly Efficient and Selective Synthesis of Renewable Isoprene Over Mo‐Fe‐O and MgO/Mg(OH)2 Composite Catalysts - Xu, Lulu; Liu, Shuo; Li, Shikun; Wang, Lei; Meng, Xiangju; Xiao, Feng‐Shou; De Baerdemaeker, Trees; Parvulescu, Andrei‐Nicolae; Zhang, Weiping (Chemistry : a European journal, 2025)
Synthesis of renewable isoprene continues to attract significant interest, yet catalysts still need improvement for industrial applications. We report herein an efficient and novel Prins tandem approach for highly selective production of isoprene from bio‐based methanol and isobutene over Mo‐Fe−O and MgO/Mg(OH)2 acid‐base bifunctional catalysts. Hydration decreases the number of strong basic sites O2− ions and increases OH groups over MgO, thus improving the isoprene selectivity. Basic OH on Mg(OH)2 promotes the Prins condensation of formaldehyde and isobutene, while acidic OH promotes dehydration of isoprenol to isoprene. Suitable contents and proportions of basic and acidic OH groups over Mg(OH)2 increase isoprene selectivity and methanol conversion to 90 and 92 % on the Mo‐Fe−O+Mg(OH)2 composite catalysts, respectively. It exhibits good recycling stability, with isoprene selectivity remaining 90 % after five successive regenerations. DFT calculations reveal OH groups formed after hydration reduce the energy barrier of the H transfer step, thereby promoting the overall reaction. Direct synthesis of renewable isoprene from bio‐sourced methanol and isobutene was achieved via a novel Prins tandem route on Mo−Fe oxide and MgO/Mg(OH)2 composite catalysts. Spectroscopic characterization experiments together with DFT calculations reveal that the excellent catalytic performance is closely related to the appropriate proportion of basic and acidic OH groups after MgO hydration.